(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Sickle cell anaemia is a type of haemoglobin disorder causing morbidity and mortality in many countries. The disease is incurable and therefore requires symptomatic management to improve quality of life. Because the alternative system of medicine can play a significant role in the management of quality of life in sickle cell anaemia, lot many combinations and formulations are attempted across many countries. Unfortunately, very few have reached a preclinical and clinical research level. In the current case study, T-AYU-HM Premium was evaluated as per the standard parameters, and a clinical evaluation considering its effect and safety was performed in this case report of a 24-year-old male with a history of sickle cell disease in hereditary. History was 8 times blood transfusion and 7 times hospitalization in past two year. He was infected with covid-19 and hospitalized, recovered with T-AYU-HM Premium only. Next month because of joint pain, fever, and weakness he visited the daycare clinic. On complete physical and laboratory examination he was started on T-AYU-HM Premium 300mg two tablets twice a day. During 6 months of treatment, he had complained of pain only thrice for which analgesics were prescribed, and no blood transfusion was required. During this 6 month period, there is a remarkable improvement in his haemoglobin, red blood corpuscles, white blood cells, and platelets. There were no untoward complaints from him suggesting that T-AYU-HM Premium exhibited its potential in sustaining the cellular integrity and thereby preventing the lysis of red blood corpuscles. The improvement in laboratory parameters, clinical parameters and established studies indicated that T-AYU-HM Premium is safe and exhibit an observational effect on red blood corpuscles of sickle cell anaemia patient.